2013
DOI: 10.1086/674439
|View full text |Cite
|
Sign up to set email alerts
|

Intersectin‐1s: An Important Regulator of Cellular and Molecular Pathways in Lung Injury

Abstract: Acute lung injury (ALI) and acute respiratory distress syndrome (ARDS) are severe syndromes resulting from the diffuse damage of the pulmonary parenchyma. ALI and ARDS are induced by a plethora of local or systemic insults, leading to the activation of multiple pathways responsible for injury, resolution, and repair or scarring of the lungs. Despite the large efforts aimed at exploring the roles of different pathways in humans and animal models and the great strides made in understanding the pathogenesis of AL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 210 publications
(342 reference statements)
1
11
0
Order By: Relevance
“…Acute lung injury (ALI) or mild acute respiratory distress syndrome (ARDS), according to the Berlin definition ( Ranieri et al, 2012 ), are associated with excessive apoptosis of endothelial and epithelial cells ( Henson and Tuder, 2008 ; Le et al, 2008 ; Predescu et al, 2013 ). Although apoptosis might induce pulmonary endothelial and epithelial barrier dysfunction leading to pulmonary edema, evidence suggests that apoptosis plays a beneficial role during ALI resolution owing to the pro-regenerative role of clearance of apoptotic cells ( Predescu et al, 2013 ; Schmidt and Tuder, 2010 ). This effect is mediated through the production of growth factors including TGFβ by macrophages engulfing apoptotic cells, or perhaps by other vascular cells ( Bardita et al, 2013 ; Henson and Tuder, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute lung injury (ALI) or mild acute respiratory distress syndrome (ARDS), according to the Berlin definition ( Ranieri et al, 2012 ), are associated with excessive apoptosis of endothelial and epithelial cells ( Henson and Tuder, 2008 ; Le et al, 2008 ; Predescu et al, 2013 ). Although apoptosis might induce pulmonary endothelial and epithelial barrier dysfunction leading to pulmonary edema, evidence suggests that apoptosis plays a beneficial role during ALI resolution owing to the pro-regenerative role of clearance of apoptotic cells ( Predescu et al, 2013 ; Schmidt and Tuder, 2010 ). This effect is mediated through the production of growth factors including TGFβ by macrophages engulfing apoptotic cells, or perhaps by other vascular cells ( Bardita et al, 2013 ; Henson and Tuder, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…We have recently shown that in vivo deficiency of ITSN-1s, an isoform of ITSN-1 that is highly prevalent in lung endothelium and deficiency of which is relevant to the pathology of ALI/ARDS ( Bardita et al, 2013 ; Predescu et al, 2013 ), induces extensive lung endothelial cell apoptosis and injury; after only 7 days of ITSN knockdown (KD-ITSN), the remaining endothelial cells exhibited phenotypic changes including hyperproliferation and apoptosis resistance against ITSN-1s deficiency, leading to increased microvessel density, repair and remodeling of the injured lung. Under pathological conditions, dysfunctional endothelial cells also show altered intracellular trafficking and signaling of cell surface receptors, such as TGFβ-RI, which is implicated in the pathogenesis of ALI/ARDS ( Kranenburg et al, 2002 ; Morrell et al, 2001 ; Sehgal and Mukhopadhyay, 2007 ; Voelkel and Cool, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…Acute lung injury is associated with excessive apoptosis of pulmonary endothelial and epithelial cells, which induce endothelial and epithelial barrier dysfunction leading to pulmonary edema [ 67 , 68 ]. Acute lung injury is triggered by direct injury to the lung and can be secondary to other inflammatory conditions such as sepsis, pancreatitis or transfusion rejection.…”
Section: Introductionmentioning
confidence: 99%
“…Acute lung injury is triggered by direct injury to the lung and can be secondary to other inflammatory conditions such as sepsis, pancreatitis or transfusion rejection. Studies have shown that apoptotic pulmonary cells or macrophages engulfing apoptotic cells release substances such as growth factors, and create conditions that favor the emergence of apoptosis-resistant cells [ 68 , 69 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation